Activity of Proteolytic and Amylolytic Enzymes from Bacillus spp. Isolated from Shrimp Ponds - IT JAMILAH; ANJA MERYANDINI; IMAN RUSMANA; ANTONIUS SUWANTO; NISA RACHMANIA MUBARIK (Microbiology Indonesia, 2009)
Accumulation of feed excess in commercial shrimp ponds due to overfeeding could decrease water quality. Protein and starch are the primary components of shrimp feed. This study was conducted to characterize extracellular proteases and amylases of Bacillus spp. isolated from shrimp ponds. 72 proteolytic and amylolytic Bacillus spp. isolates were screened from shrimp ponds in Karawang, West Java. Ten isolates were selected for further characterization for their growth and ability to reduce total suspended solid generated from commercial shrimp feed. Bacillus sp. DA 5.2.3 and L5 showed excellent activity in reducing total suspended solid, by 37 and 30% respectively. Protease and a-amylase activities of Bacillus sp. DA 5.2.3 isolate were consistently higher than that of L5. Maximum total and specific protease activity of DA 5.2.3 isolate was 2.0 U mL-1 and 40.9 U mg-1 respectively, while the activities of the L5 isolate were 2.1 U mL-1 and 23.0 U mg-1 respectively. Based on its 16S rRNA gene sequences, Bacillus sp. DA 5.2.3 showed 99% similarity to Bacillus cereus XHJ-2-6. Bacillus sp. DA 5.2.3 could potentially be applied to maintain water quality by reducing total suspended solid in water columns of shrimp ponds.